Nursing Care for Hydronephrosis Patients Through Deep Breathing Relaxation Techniques Implementation to Reduce Pain: A Case Report - Miftah Salsabila; Muhamad Zulfatul A'la; Murtaqib; Yudho Tri Handoko (KHD Production, 2025)
Hydronephrosis occurs due to a disorder in the urinary tract that causes the flow of urine from the urinary tract to be obstructed, causing the dilation of the channels in the kidneys. The main symptoms that hydronephrosis patients commonly feel are pain in the lower back, nausea, and fatigue. Deep breath relaxation therapy, as a non-pharmacological therapy, has the effect of reducing pain. This study aims to determine the effect of deep breath relaxation techniques in patients with hydronephrosis and pain complaints. The method used in this study was a case study of one patient who was given an intervention for three days. The pain intensity scale was measured using the Numeric Rating Scale (NRS). This study showed a significant reduction in pain intensity in hydronephrosis patients from a scale of 6 to a scale of 3, where the deep breath relaxation technique intervention was given for three consecutive days for three sets per day in patients. Based on the results of the study, the researcher suggests the use of deep breath relaxation techniques as a non-pharmacological therapy in hydronephrosis patients with pain complaints in clinical practice, which can be provided by health workers, especially nurses or as patient-independent therapy because deep breath relaxation techniques are easy to do therapy and do not require additional tools and materials to do so.